Gestão inteligente utilizando o software Olha O Ônibus - RODRIGUES, Roberto de Oliveira (2024)
This work presents the results achieved through the execution and fulfillment of the objectives and goals of the extension project entitled Smart Management Using the Olha o Ônibus Software. The preparation of this document considered the results achieved based on the objectives and goals outlined. Through this extension project, the software continued to be improved to collaboratively assist public transportation users in finding information about public transport routes, especially bus stops or selected locations during their journeys. Its duration covered the period from 08/2023 to 07/2024, and it was completed at the time of this work's production. We emphasize that the project's objectives and goals were partially achieved, as will be detailed below.